PENGARUH CITRA USAHA DAN PRODUK UMKM RAMAH LINGKUNGAN TERHADAP KEPUASAN DENGAN KEPERCAYAAN SEBAGAI MEDIASI - Yogi Saputra; Endang Tjahjaningsih (Jurnal Pendidikan Ekonomi (JURKAMI), 2026)
This study aims to examine and analyze the effects of corporate image and environmentally friendly products on customer satisfaction, with customer trust serving as a mediating variable at CV. Mendong Jaya Tasikmalaya Handicraft MSME. The study employed a quantitative approach using an explanatory research design. The population comprised all customers of CV. Mendong Jaya Tasikmalaya Handicraft MSME, with a sample of 100 respondents selected through a non-probability sampling technique. Data were collected using a questionnaire that had been tested for validity and reliability. Data analysis was conducted using multiple regression analysis and the Sobel test to examine both direct and indirect (mediating) effects among the variables. The findings indicate that corporate image has no significant effect on either customer trust or customer satisfaction. In contrast, environmentally friendly products have a positive and significant effect on both customer trust and customer satisfaction. Customer trust also has a positive and significant effect on customer satisfaction. Furthermore, customer trust does not mediate the relationship between corporate image and customer satisfaction but significantly mediates the relationship between environmentally friendly products and customer satisfaction at CV. Mendong Jaya Tasikmalaya Handicraft MSME.